2023
DOI: 10.1149/11106.1013ecst
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microstructure on the Sulfur Tolerance of Ceria-Based Anodes in Low Temperature SOFC

Abstract: Hydrocarbon fuels such as natural gas or biogas commonly contain small amounts of impurities like sulfur which result in a strong degradation of the polarization resistance (R pol) in Ni/YSZ anodes. The sulfur poisons the nickel catalyst and hinders the electrooxidation of hydrogen. At common SOFC operation temperatures above 700 °C the R pol of a Ni/GDC anode is less influenced. The trend to a significantly lower operating temperature of SOFCs even below 600 °C raises the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…[25][26][27][28] The trend of operating SOFC-systems at a much lower temperature even below 600 °C29,30 enables the application of nanostructured electrodes with high performance and durability. [31][32][33] Previous studies revealed that an infiltration of nickel/ceria (forming nanoparticles during annealing) leads to a significant increase in performance and/or sulfur tolerance compared to a pure Ni/GDC cermet, 5,24,34,35 single phase GDC 23,34,36,37 or Ni/YSZ 5,38,39 fuel electrodes without infiltration. Primdahl et al 37 compared the performance of GDC fuel electrodes sintered on an 8YSZ substrate with and without nickel infiltration between 700 and 1000 °C and observed a significant improvement of the GDC fuel electrode with Ni-infiltration especially at lower operation temperatures.…”
mentioning
confidence: 99%
“…[25][26][27][28] The trend of operating SOFC-systems at a much lower temperature even below 600 °C29,30 enables the application of nanostructured electrodes with high performance and durability. [31][32][33] Previous studies revealed that an infiltration of nickel/ceria (forming nanoparticles during annealing) leads to a significant increase in performance and/or sulfur tolerance compared to a pure Ni/GDC cermet, 5,24,34,35 single phase GDC 23,34,36,37 or Ni/YSZ 5,38,39 fuel electrodes without infiltration. Primdahl et al 37 compared the performance of GDC fuel electrodes sintered on an 8YSZ substrate with and without nickel infiltration between 700 and 1000 °C and observed a significant improvement of the GDC fuel electrode with Ni-infiltration especially at lower operation temperatures.…”
mentioning
confidence: 99%